MAPPING POTENTIAL REGION OF THE AGRICULTURAL SECTOR AREA TO INCREASE ECONOMIC DEVELOPMENT IN PENAJAM PASER UTARA REGENCY - Kumalawati, Rosalina; Pratomo, Rahmat Aris; Budiman, Puput Wahyu; Saputra, Erlis; Susanti, Ari; Rijanta, Rijanta; Raharjo, Jany Tri; Danarto, Wisnu Putra; Murliawan, Karnanto Hendra; Yuliarti, Astinana; Muhtar, Ghinia Anastasia; Anggraini, Rizki Nurita (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Lambung Mangkurat, 2023)
Indonesia is an agricultural country and a developing country which has the potential for inequality in development. Inequality in development is increasingly felt in several areas, including Jakarta. As Jakarta becomes more densely populated with increasingly complex problems, there is talk of moving the nation's capital to East Kalimantan Province. North Penajam Paser Regency is one of the locations for moving the new national capital. It is hoped that the relocation can overcome population problems and development inequality. Developmental inequality will continue to occur if it does not receive serious attention. Development inequality can be overcome by paying attention to regional potential, especially in the agricultural sector. Seeing this, it is very necessary to carry out research with the title